An analysis of the annulment mechanism under ICSID Jurisprudence - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2017)
The International Centre for Settlement of Investment Disputes (ICSID) is celebrating its halfcentury existence this year. Having presided over more than 525 cases in various topics including annulment; it is no surprise that it is described as the premier international investment arbitration institution in the world. Annulment was designed as an exceptional remedy to safeguard against violation of fundamental legal principles. This provision, enshrined in the ICSID Convention of 1966, stands out as the 'art', 'crown' and 'jewel' of ICSID jurisprudence. The annual number of cases registered by ICSID increased rapidly in the last decade. To date, there are 160 signatories and contracting states to the ICSID Convention. Awards rendered under this mechanism are binding and have been successfully implemented without interference by domestic courts. What this statistic fails to show is that the rate of annulment has increased considerably. This implies that out of every 344 arbitration cases registered; 150 ICSID Convention awards have been rendered and 53 annulment proceedings instituted. This is against the background that only few annulment applications existed in the institutions' early years. This remedy has been pursued by both claimants and respondents to ICSID proceedings. Approximately 57 percent of annulment proceedings have been initiated by respondents (in all instances, states), 36 percent by claimants and 7 percent by both parties. The annulment mechanism is deployed by ICSID in lieu of providing an appellate option. Dissatisfied parties have employed this mechanism to challenge awards rendered by the institution. It follows that, despite the institution's uniqueness and widely recognised success in international arbitration, annulment negates the principle of finality and certainty ? one of the core principles of arbitration. The above flaw has led to the withdrawal of Latin America countries from the ICSID Convention. Bolivia was the first to withdraw as it denounced its membership in 2007. This was followed by Ecuador in 2010 and Venezuela in 2012. Countries like the United States, South Africa and Germany have also revisited this provision and called for review of the whole system. This research calls for reform of the ICSID annulment mechanism. It arrives at practical alternatives to be adopted by the institution aimed at creating finality and predictability in the international arbitration system. This mini-dissertation argues that finality and predictability can be achieved under ICSID by establishing an appellate mechanism drawing lessons from the institutional framework of the World Trade Organization Appellate Body Dispute Settlement System (WTO - DSS). If the annulment mechanism negates the principle of finality in international arbitration, then the ICSID objective of attaining predictability in international arbitration remains fictitious. This research therefore adds to the growing voice that argues that amendment of the annulment procedure is long overdue.